Retrofitting Javanese Traditional Games as Indonesia Culture Identity: Providing English Vocabulary - Suhono Suhono; Yeasy Agustina Sari (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2017)
A traditional Javanese game was one of the cultures inherited of hereditary society which has great value to society, specifically to educate the children. Unfortunately, the impact a lot of modern games in modern era from other countries has demolished the position of local games. It seem gave negative impact for children today. They tend to focus on new game (download new game continuously) in Googleplay store without understanding educative value of itâ€™s game. Consequently the children abandon traditional Javanese game and leave educative game. The researcher aimed to retrofit traditional Javanese games to provide English vocabulary for children in order to motivate them in Learning English. To solve the problem the researcher adapted Kemp and Yalden model of instructional program design to retrofitting Javanese traditional game. The result showed that Javanese traditional games: Learning alphabet was the result retrofitted from Sobyong game, Learning days was the result retrofitted from Engklek game, Learning Colors was the result retrofitted from â€œJamuranâ€ game, and Learning part of body was the result retrofitted from "Oyak- Oyakan". These modification games could be enjoyedinEnglish vocabulary learning process. Key words: Retrofitting Javanese Traditional Games, Sobyong, Jamuran, Engklek, Oyak â€“ oyakan, English Vocabulary,